Application of laparoscopy in current fertility practice - Jani, Rajita S.; Munshi, Devangi S.; Jani, Shashwat K.; Munshi, Sanjay P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The present study is carried out with the objective of establishing the role of diagnostic and operative laparoscopy as a simple, safe and accurate tool in the evaluation of infertility. The aims of current study were to study the application of laparoscopy in current fertility practice, to evaluate indications for diagnostic laparoscopy for infertility, to study findings of diagnostic laparoscopy and to study various operative procedures performed for correction of infertility. Methods: This is a prospective study of 50 women undergoing infertility workup in a private hospital from January 2011 to January 2012. All infertile women having primary or secondary infertility were included in the study. Couples having male factor infertility were excluded from the study. Data were collected and analyzed. Results: Our study is conducted in 50 cases of infertility patients out of which 74% were primary infertility and 26% were secondary infertility. Uterine factors were found in 16% of cases, tubal factors were found in 44% of cases, ovarian factors were implicated in 30% of cases out of which majority (12%) had PCOD. Among the peritoneal factors (18%) endometriosis and pelvic adhesions were found in 6% each. Inspite of thorough laparoscopic evaluation no cause (unexplained infertility) was found in 14% of cases and hence overall, the pelvic pathology was found in 86% of cases. Conclusions: Laparoscopy is the gold standard for diagnosing tubal and peritoneal disease, endometriosis, adhesions and other pelvic pathology, because no other imaging technique provides the same degree of sensitivity and specificity.